Experimental study of pyrolysis-combustion coupling in a regeneratively cooled combustor: Heat transfer and coke formation. (1st March 2019) - Taddeo, L.; Gascoin, N.; Chetehouna, K.; Ingenito, A.; Stella, F.; Bouchez, M.; Le Naour, B.
Highlights: An innovative fuel-cooled combustor is set-up. The sensible and chemical heat sink absorbed by the decomposing fuel are determined. The cooling system heat exchange efficiency is investigated. Fuel coking activity is analyzed and quantified. A coking monitoring method suitable for on-board application is validated. Abstract: Scramjets engines are suitable to propel high-speed hypersonic vehicles. As flight velocities increase, vehicle thermal protection becomes very critical. In this sense, regenerative cooling is a well-known cooling technique, particularly effective when an endothermic hydrocarbon is used as fuel. The development of regeneratively cooled engines faces several challenges, the most important being the difficulty of defining an engine regulation strategy because of the dual function of the fuel (both propellant and coolant). In this context, a regeneratively cooled combustor allowing the experimental study of a fuel-cooled engine has been designed. Experiments are run using ethylene as fuel and air as oxidizer. Two command parameters, i.e. fuel mass flow rate and equivalence ratio (1.0–1.5), are investigated. It has been observed that fuel mass flow rate increases by 16–20% result in heat flux density (from the combustion gases to the combustor wall) increases between 20 and 28%, depending on equivalence ratio and pressure. The dependence of the cooling system heat exchange efficiency on the two operating parameters has been demonstrated. Ethylene coking activity has been investigated. For applied interest, a monitoring method for carbon deposits formation has been developed and validated.